Eucalyptus globulus essential oil increased neovascularization and vascular endothelial growth factor expression in male wistar rats exposed to UVB - Noviana Indrawati; Ida Sri Iswari; Ni Wayan Winarti (Indoscholar, 2021)
Background: Eucalyptus globulus essential oil contained 1,8-cineol, which may accelerate wound healing. This study aimed to prove Eucalyptus globulus essential oil's effect on increasing neovascularization and Vascular Endothelial Growth Factor (VEGF) expression in Wistar rats skin exposed to ultraviolet B (UVB). Methods: A Post-test only controls group study design was applied on 36 male Wistar rats, aged 3-4 months old, weighing 150-200 grams. The animal subject was exposed to UVB (65 mJ/cm2, 65 seconds for seven days), injured on their back using a punch biopsy with a diameter of 10 mm, and divided into two groups. For seven days, on the wound, the control group was given 2 cc of 0.9% NaCl twice a day, while the treatment group was given Eucalyptus globulus essential oil (2 cc). Both groups were given oral Amoxicillin three times a day. The skin tissue was taken on day eight to assess neovascularization and VEGF expression. Results: The results show that neovascularization in the treatment group was higher than in the control group (p < 0.05). Meanwhile, the median VEGF expression in the treatment group was also higher than in the control group (p < 0.05). Conclusions: Topical administration of Eucalyptus globulus essential oil increased neovascularization and VEGF expression in the skin of male Wistar rats injured and exposed to UVB. Further research is needed to assess the effectiveness of the essential oil in enhancing neovascularization and VEGF expression in humans with multiple exposures at different doses to optimize the wound-healing effect.